CONTRIBUTIONS OF CAD / CAE TECHNOLOGY IN DEVELOPMENT PROJECTS OF AGRICULTURAL MACHINERY AND IMPLEMENTS: A CASE STUDY - Flavio Ricci Martinez (Iberoamerican Journal of Project Management, 2017)
This work aims to understand the contributions of CAD / CAE technology development projects Agricultural Machinery and Implements. The segment of Agricultural Machinery and Implements part of capital goods, which provides items that will be used to produce goods and services in other sectors and that is strategic in many economically and for innovation and technological diffusion in the country sector. To achieve the proposed objective a case study was conducted at a manufacturer of this type of product (combines, planters, tractors, etc.) located in the region of Ribeirão Preto. Among the main contributions can excel found to reduce the time and costs of the project, the largest customer interaction, integration with the staff and the increased ability to test alternative solutions for solving problems.